2010
DOI: 10.3109/13693780902964339
|View full text |Cite
|
Sign up to set email alerts
|

Absence of TLR2 influences survival of neutrophils after infection withCandida albicans

Abstract: Candida albicans is an opportunistic pathogen, which causes local and/or disseminated diseases in immunosuppressed humans. Phagocytic cells play a critical role in the immune response against C. albicans. Toll like receptors (TLR) are important in the identification of invading microorganisms and in the regulation of neutrophil survival. TLR2 has been shown to participate in the response against pathogenic yeasts and to increase the functional life span of neutrophils. In view of these observations, we studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 42 publications
1
18
1
Order By: Relevance
“…Studies with TLR2 knockout mice showed both resistance (Netea et al, 2004b) or susceptibility to primary or secondary systemic C. albicans infection (Gil et al, 2005; Hise et al, 2009), while TLR2 knockout macrophages showed impaired fungal clearance (Blasi et al, 2005), with both impairment or enhancement of pro-inflammatory cytokine production (especially TNF-α; Blasi et al, 2005; Gil and Gozalbo, 2006). The absence of TLR2 also decreased chemotaxis rate of murine neutrophils, together with decreased fungal killing mechanisms and survival of these cells (Tessarolli et al, 2009). TLR2 is probably not directly involved with humoral response after secondary C. albicans systemic infection, since this parameter was not altered in TLR2 knockout mice (Villamón et al, 2004).…”
Section: Infectious Diseases and The Role Of Tlr2mentioning
confidence: 99%
“…Studies with TLR2 knockout mice showed both resistance (Netea et al, 2004b) or susceptibility to primary or secondary systemic C. albicans infection (Gil et al, 2005; Hise et al, 2009), while TLR2 knockout macrophages showed impaired fungal clearance (Blasi et al, 2005), with both impairment or enhancement of pro-inflammatory cytokine production (especially TNF-α; Blasi et al, 2005; Gil and Gozalbo, 2006). The absence of TLR2 also decreased chemotaxis rate of murine neutrophils, together with decreased fungal killing mechanisms and survival of these cells (Tessarolli et al, 2009). TLR2 is probably not directly involved with humoral response after secondary C. albicans systemic infection, since this parameter was not altered in TLR2 knockout mice (Villamón et al, 2004).…”
Section: Infectious Diseases and The Role Of Tlr2mentioning
confidence: 99%
“…Notably, the lack of TLR2 impairs the early recruitment as well as killing capacity of neutrophils against A. fumigatus (Meier et al, 2003; Bellocchio et al, 2004a). Similarly, fewer neutrophil/monocytes are recruited in TLR2 −/− mice in comparison to wild-type animals at day 1 after post-peritoneal infection with live C. albicans (Tessarolli et al, 2010). Interestingly, upon intraperitoneal challenge with heat-killed C. albicans , TLR2 defficiency has no effect on early (4 h) phagocyte recruitment, but results in an enhanced macrophage recruitment in mutant versus control mice at day 3 after infection (Netea et al, 2004).…”
Section: Fungal Sensing By Toll-like Receptorsmentioning
confidence: 99%
“…Additionally, the use of live versus heat-killed Candida cells may affect both kinetics and nature of recruited phagocytes. Phagocytes emerging at day 1 of post-peritoneal infection with live Candida exhibit impaired nitric-oxide release, myeloperoxidase activity, chemokine, and cytokine production, as well as neutrophil survival in the absence of TLR2 (Tessarolli et al, 2010). Thyoglycolate-elicited TLR2 −/− neutrophils and macrophages show reduced phagocytic activity toward C. albicans than their wild-type counterparts (Tessarolli et al, 2010).…”
Section: Fungal Sensing By Toll-like Receptorsmentioning
confidence: 99%
See 2 more Smart Citations